PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Rumah Sakit Panti Wilasa â€œCitarumâ€ Kota Semarang) - Al Rizal, M. Hanif; Ratnawati, Intan (Diponegoro Journal of Management, 2012)
Receiving proper healthcare is a primary need in society. Qualified healthcare canâ€™t be apart from the optimal work performance of all parties in the healthcare industry, to this matter is from its employees. A good work performance can emerge if the employees applied the main values that organization used as its philosophies and guidance in order to run its activities, called organizational culture. The optimal work performance also can be yielded from the employees who like their job and comfortable with it, where they can obtain their job satisfaction according as they expected. The aim of this research is to analyze the effect of organizational culture and job satisfaction to the employee performance in Panti Wilasa â€œCitarumâ€ Semarang Hospital. Sample applied in this research is 100 employees. The data collected by using questionnaires which the sampling technique is simple random sampling. Analytical method used in this research is multiple linear regression analysis, using SPSS program. The result shows that organizational culture positively influence on employee performance, and job satisfaction positively influence on employee performance. Empirical finding indicated that to increase employee performance, the management should pay more attention to organizational culture factors and job satisfaction factors, because those factors proved influence on employee performance.